The Effect of ICG and Capital Adequacy on the Value of the Company with ISR as a Moderating Variable - Khainun Muflikhah; Fetria Eka Yudiana (Fakultas Ekonomi, UIN Maliki Malang, 2022)
This study aims to test the influence of Islamic corporate governance and capital adequacy on the value of companies with Islamic social reporting as moderating variables. The data used in this study was obtained from islamic commercial bank data 2014-2020, using purposive sampling techniques obtained by 8 (eight) Islamic commercial banks that meet the criteria to be used as research samples. To test this research hypothesis, a multiple linear regression model was used with the help of the Eviews 10 program. Analytical techniques used in the study include stationarity tests, panel data regression tests, and classical assumption tests. Partial test results showed a positive and significant influence of Islamic Corporate Governance (ICG) and Islamic Social reporting (ISR) on the value of the company while capital adequacy had no significant effect on the value of the company. And the results of moderate regression analysis showed the result that ISR can moderate the relationship between ICG and company value whereas the relationship of capital adequacy with company value cannot be moderated by ISR.